2022
DOI: 10.3390/ijerph19095710
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on the Quantity of Bisphenol A in Bottled Drinking Water

Abstract: Bisphenol A (BPA) is a component used in the production of polycarbonate plastics (PC) and epoxy resins, which are currently widely used in food and beverage packaging. Although BPA is not used in polyethylene terephthalate (PET) manufacturing, a recent study reported its presence in PET water bottles. This study was conducted to investigate the effects of storage conditions on the release of BPA from PET bottles as well as to assess health risks associated with the consumption of bottled water. Using high-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…However, there is a reasonable concern regarding how precise or realistic food simulants simulate real food mixtures, especially in the various conditions of temperature, light, pH, storage time or contact area [52,53]. Some authors speculate that food simulants could be useful in some cases, but the final risk assessment can be performed only using data from BPA migration analyses with real food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a reasonable concern regarding how precise or realistic food simulants simulate real food mixtures, especially in the various conditions of temperature, light, pH, storage time or contact area [52,53]. Some authors speculate that food simulants could be useful in some cases, but the final risk assessment can be performed only using data from BPA migration analyses with real food.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors [45,46,48,51,56,57] suggest that humans are almost ubiquitously exposed to BPA and food contamination that might come from different sources, such as contact material during cleaning and contact material during preparation, along with different packaging materials that might have a cumulative effect. Ginter-Krmarzyk et al [52] demonstrated that even though the individual concentrations of BPA in bottled water might be low (ng L −1 ) at 0.6 mg kg −1 per body weight, the cumulative daily dose in the body may be much higher than the quoted concentrations due to the number of products containing BPA. It should be kept in mind that food processing technology itself could be a source of BPA contamination in food and water [17,[58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that trademarks and packaging should be considered a significant factor in BPA migration from PC polymers (Errico et al, 2014; Santillana et al, 2013). Different conditions in commercial bottle manufacturers, such as molding condition, annealing process, residual BPA in the resin, moisture content, and installation to draw water and to fill the bottles, could lead to BPA release into the container content (Ginter‐Kramarczyk et al, 2022; Mercea, 2009). In the manufacturing process, the airborne BPA could be blown and entered into plastics during the air expansion process (Holmes et al, 2021).…”
Section: Bpa Release Conditionsmentioning
confidence: 99%
“…BPA is an important chemical used as a monomer for PC [148], antioxidant or plasticizer in PP, PE, PVC, epoxy resins and coating used to line the packaging of food and beverage cans [149,150]. It has been reported that BPA migrates out of PC, epoxy resins and other consumer plastics [151] and may contaminate food products and drinks [152,153], producing adverse effects on human health, such as liver and pancreatic function alternation and respective changes in insulin resistance. BPA leaching also affects the development of offspring in the wombs of pregnant women, causing issues with brain function [154,155] and inhibiting thyroid hormone-mediated transcription by acting as an antagonist [156].…”
Section: Potential Toxicological Effects Of Micro-and Nanoplastics Fr...mentioning
confidence: 99%